ANALISIS PENGATURAN SOFT HANDOVER OVERHEAD TERHADAP PEFORMANSI KAPASITAS TRAFIK NODE-B DI PT. TELKOMSEL PONTIANAK - Edy Chandra . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2017)
ABSTRACT This research explained about the effect of traffic Node-B capacity ( we can mention BTS on GSM network) toward Soft Handover Overhead setting on 3G network that implementation in PT.Telkomsel Pontianak. Which Note-B TB. Arang Limbung 2 as sample has experienced full capacity traffic and coused many discountinuance connection on moved situation, we can see on software NetAct value Soft Handover  <99% this is constituted   of   value   that   not   expected   from   PT. Telkomsel, becouse the standard value PT. Telkomsel should  more than >99%.  The Soft  Handover  Overhead method   apparoutly   can   gave   change   toward   Soft Handover  value is by changed parameter CPICH offset from 0 into -20. The incroased kinds of network draw the total  uer.  Many  of  user  can  coused  slop  the  network quality becouse raising of interference network or traffic voice  and  the  high  data.  Node-B  is  sets  of equipment radiator and accept that gave radio service to UE, Node-B also has maximum capacity limited. When the capacity full  then coused  drop call  and  ms try attempt  rejected because channel capacity Node-B total decreased and not optimum so can coused the process Soft Handover filled. The  monitor  of Node-B  data  who hs disturbance  used netAct aplication and look the slop value of Note-B Soft Handover  under 99%, it means so many discounnected call  on  moved  situation.  Node-B  TB.  Arang  Limbung 2has lower value Soft Handover  until <98,44% from 3 mei 2016 – 9 mei 2016. The value CPICH offset used is - 20. Which the process of Soft Handover  Overhead is to increase the value CPICH offset lower than 0. The value of Soft Handover success rate total everyday is 98,44% before used Soft Handover Overhead method the total everydat increased until 99,62% Soft Handover   success rate is to precentation the total success handover alloted the total handover occur, the result of this research show that the mechanism Soft Handover good after done Soft Handover Overhead method.   Keyword   :   NetAct,   CPICH   offset,   Soft   Handover Overhead